Answer:
1)
![sin \left((- \pi)/(12) \right) = ((√(2) - √(6) )/(4)](https://img.qammunity.org/2022/formulas/mathematics/college/q0lwvyu07p6z6t9f1zx7q4upllom2c0hrw.png)
2)
![tan\left(( \pi)/(12) \right) = 2 - √(3)](https://img.qammunity.org/2022/formulas/mathematics/college/7jh7ajzu2nxsyyvdyklk1fz7767ocgr7j5.png)
3)
![tan\left(( 5\cdot \pi)/(12) \right) = 2 + √(3)](https://img.qammunity.org/2022/formulas/mathematics/college/gsel4geg1u1qwvc8bvio02pz9xbgp8zvpv.png)
Explanation:
1)
![sin \left((- \pi)/(12) \right) = sin(-15^(\circ))](https://img.qammunity.org/2022/formulas/mathematics/college/dvqav6uol82qf807zojwogtjfe4zb0g5nx.png)
sin(-15°) = sin(30° + (- 45°)) = sin(30°)cos(-45°) + cos(30°)sin(-45°)
sin(30°)cos(-45°) + cos(30°)sin(-45°) = 1/2 × (√2)/2 + (√3)/2 × (-√2)/2
1/2 × √2/2 + √3/2 × -√2/2 = (√2)/4 - (√6)/4 = ((√2) - (√6))/4
sin(-15°) = ((√2) - (√6))/4
![sin \left((- \pi)/(12) \right) = sin(-15^(\circ)) = ((√(2) - √(6) )/(4)](https://img.qammunity.org/2022/formulas/mathematics/college/bh48p2n0v71z696pxufoe7qr2ev3dvv09k.png)
2)
![tan\left(( \pi)/(12) \right) = tan(15^(\circ))](https://img.qammunity.org/2022/formulas/mathematics/college/mvrwsej9c4yh1zocajalwg97b0b7uc1hz5.png)
tan(15°) = tan(45° + (-30°)) = (tan(-30°) + tan(45°))/(1 - tan(-30°)×tan(45°))
(tan(-30°) + tan(45°))/(1 - tan(-30°)×tan(45°)) = ((-1/√3) + 1)/(1 - (-1/√3))
((-1/√3) + 1)/(1 - (-1/√3)) = (3 - √3)/(3 + √3) = (3 - √3)·(3 -√3)/((3 - √3)·(3 + √3))
(3 - √3)·(3 -√3/((3 - √3)·(3 + √3)) = (9 - 6·√3 + 3)/(9 - 3) = (12 - 6·√3)/6
(2 - √3)
![tan\left(( \pi)/(12) \right) = tan(15^(\circ)) = 2 - √(3)](https://img.qammunity.org/2022/formulas/mathematics/college/vdalqx6g21rt3agpjofzx1v6llms0kptwn.png)
3)
![tan\left(( 5\cdot \pi)/(12) \right) = tan(75^(\circ))](https://img.qammunity.org/2022/formulas/mathematics/college/8as4j02gsjgy8j5jddyg79qff5lh6ee6ah.png)
tan(75°) = tan(30° + 45°) = (tan(30°) + tan(45°))/(1 - tan(30°)×tan(45°))
(tan(30°) + tan(45°))/(1 - tan(30°)×tan(45°)) = ((1/√3) + 1)/(1 - 1/√3)
((1/√3) + 1)/(1 - 1/√3) = (3 + √3)/(3 - √3) = (3 + √3)·(3 +√3/((3 - √3)·(3 + √3))
(3 + √3)·(3 +√3/((3 - √3)·(3 + √3)) = (9 + 6·√3 + 3)/(9 - 3) = (12 + 6·√3)/6
(12 + 6·√3)/6 = 2 + √3
![tan\left(( 5\cdot \pi)/(12) \right) = tan(75^(\circ)) = 2 + √(3)](https://img.qammunity.org/2022/formulas/mathematics/college/jh6vz8neczm0rbk3qyacompxter0scxqhp.png)